How provincial is your region? Effects on labour productivity in Europe - Alfonso Gambardella; Myriam Mariani; Salvatore Torrisi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2002)
This paper estimates the determinants of labour productivity in European NUTS regions during 1989-1996. Unlike previous studies, which have focussed either on local technological capabilities or on agglomeration economies, we compare three potential explanations of regional advantages: Technological capabilities (proxied by regional patents), agglomeration economies (employment density), and openness. To study the latter we use a new measure, the number of airplane passengers embarked and disembarked in the region, and found that in spite of some limitations, this is a meaningful index for the openness of the regions and possibly of other locations (e.g. cities). By using instrumental variables, we confirm existing results that patents and employment density affect labour productivity. Our novel finding is that openness affects labour productivity as well.
Keywords: O18; O30; O47; R11; 330; economics of technology; Arbeitsproduktivität; Regionale Wirtschaftskraft; Agglomerationseffekt; Technischer Fortschritt; Außenhandel; EU-Staaten